TREM2 in the pathogenesis of AD: a lipid metabolism regulator and potential metabolic therapeutic target - Li, Rui-Yang; Qin, Qi; Yang, Han-Chen; Wang, Ying-Ying; Mi, Ying-Xin; Yin, Yun-Si; Wang, Meng; Yu, Chao-Ji; Tang, Yi (Molecular neurodegeneration, 2022)
Triggering receptor expressed on myeloid cells 2 (TREM2) is a single-pass transmembrane immune receptor that is mainly expressed on microglia in the brain and macrophages in the periphery. Recent studies have identified TREM2 as a risk factor for Alzheimer’s disease (AD). Increasing evidence has shown that TREM2 can affect lipid metabolism both in the central nervous system (CNS) and in the periphery. In the CNS, TREM2 affects the metabolism of cholesterol, myelin, and phospholipids and promotes the transition of microglia into a disease-associated phenotype. In the periphery, TREM2 influences lipid metabolism by regulating the onset and progression of obesity and its complications, such as hypercholesterolemia, atherosclerosis, and nonalcoholic fatty liver disease. All these altered lipid metabolism processes could influence the pathogenesis of AD through several means, including affecting inflammation, insulin resistance, and AD pathologies. Herein, we will discuss a potential pathway that TREM2 mediates lipid metabolism to influence the pathogenesis of AD in both the CNS and periphery. Moreover, we discuss the possibility that TREM2 may be a key factor that links central and peripheral lipid metabolism under disease conditions, including AD. This link may be due to impacts on the integrity of the blood–brain barrier, and we introduce potential pathways by which TREM2 affects the blood–brain barrier. Moreover, we discuss the role of lipids in TREM2-associated treatments for AD. We propose some potential therapies targeting TREM2 and discuss the prospect and limitations of these therapies.